Root Canal Treatment of the Maxillary Second Molar with an Unusual Morphology: A Case Report - Desire Octarina, Lia; Endra Untara, Tri; Mulyawati, Ema (Journal of Dentistry Indonesia, 2020)
Four rooted maxillary second molar is a rare condition. A research of 1,200 maxillary second molars found only 0.4% of the sample with this condition. In a tooth with two palatal roots, one of them is the normal palatal root, while the other is a supernumerary structure which can be found mesiolingually (radix mesiolingualis) or distolingually (radix distolingualis). Objective: to describes a successful root canal treatment of a maxillary second molar with radix mesiolingualis. Final restoration using a short fiber-reinforced composite as the bottom structure under the onlay composite direct restoration. Case report: A 39-year old female patient complained of pain continuously for the past two weeks in her right maxillary second molar (tooth #17). Clinical examination revealed a deep mesioocclusal caries lesion and presence of extra cusps on the palatal surface of the crown. Conclusion: Crown with extra cusps relatively larger compared to a normal crown. It could be indicated the additional palatal roots. Those variations could be identified by clinical and radiographic examination, while more accurate assessment with CBCT imaging. The right material was required to support function and strengthen the tooth after root canal treatment.